2015
DOI: 10.1371/journal.pone.0140494
|View full text |Cite|
|
Sign up to set email alerts
|

Percutaneous Aspiration Thrombectomy for Arterial Thromboembolism during Infrainguinal Endovascular Recanalization

Abstract: ObjectivesTo evaluate the efficacy of percutaneous aspiration thrombectomy (PAT) for infrainguinal arterial thromboembolism in patients undergoing endovascular recanalization (EVR) and to investigate the predictors for thromboembolic complications.Materials and MethodsIn total, 23 patients (23 limbs) who underwent PAT for thromboembolism (PAT group, PG) during EVR and 237 patients (302 limbs) who underwent successful EVR without thromboembolic complications (control group, CG) were enrolled. Immediate post-ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Following publication of this article [ 1 ], the authors requested its retraction due to errors in the data analyses. A member of PLOS ONE ’s Editorial Board confirmed that the statistical analyses were not done correctly and as such the conclusions of the article have been called into question.…”
mentioning
confidence: 99%
“…Following publication of this article [ 1 ], the authors requested its retraction due to errors in the data analyses. A member of PLOS ONE ’s Editorial Board confirmed that the statistical analyses were not done correctly and as such the conclusions of the article have been called into question.…”
mentioning
confidence: 99%